Avaliação ecotoxicológica de tensoativos de origem química e biológica - Santos, Vanessa Santana Vieira (2018)
The employment on a global scale and the increasing release of surfactants on the ecosystems cause the accumulation of their residues on environment, consequently altering its original characteristics and whose potential impacts on organisms remain not elucidated. Ecotoxicology is an essential science regarding the assessment and knowledge about the impact of toxic compounds on biological systems. The waterflea Daphnia magna is one of the most sensitive species of ecotoxicological standardized assays. However, it is also important to consider the use of autochthonous species, such as Dendrocephalus brasiliensis, in studies performed in tropical regions, since they attend the specificities of local ecosystems and provide realistic results. In this sense, the aim of this study was to evaluate the ecotoxicological parameters for chemical surfactants – sodium dodecyl sulphate and Triton X-100 – and biogenic surfactants – surfactin, iturin and fengycin – at different concentrations using D. magna as model organism and D. brasiliensis as the representative species of tropical freshwaters. Data obtained through acute toxicity tests revealed a dose-dependent for all chemicals. D. brasiliensis showed lower EC50-48h values than D. magna considering all the tested compounds, indicating a higher sensitivity of the tropical species in relation to the species from temperate regions. The results confirmed an environmentally safe behaviour of fengycin and iturin. Nevertheless, surfactin was the less safety biosurfactant for both organisms, indicating that even biological compounds are able to cause deleterious effects on living organisms. Also, the synthetic surfactants exhibited high toxicity effects, as the compounds showed immobility impacts on both species even in low concentrations. Evaluations considering the recommended dosage revealed a higher toxicity of SDS for both species. The higher responsiveness of D. brasiliensis highlights the organism as a promising tool for ecotoxicological studies regarding tropical climates.